Family Planning in Teens - Bachmann Sánchez, Carlos (2015)
The clinical study of 262 adolescent users IUD's served in the Maternity Hospital of Lima in the space of 20 months is carried out. 86% of these adolescents reported not having used any contraceptive method before. Postpartum 56% no longer wish to have more children and 44% want to space births. 24% of them presented obstetric history and where abortion prevailed. Cohabitants, mestizo and dedicated to household chores are the vast majority of them. 12 involuntary expulsions occurred, which gives a rate of 2.7 per 100 years of use. 20 extractions were performed by pain and bleeding which gives a rate of 4.6 per 100 years of use. Five pregnancies occurred, which gives a failure rate of 1.1 per 100 years of use. 86% of users had their first control and end of the study 23% of them had four controls.